Peculiarities of pregnancy course in women with polycystic ovarian syndrome - Siusiuka, V. H.; Shevchenko, A. O.; Kyryliuk, A.; Bohuslavska, N.; Babinchuk, O.; Сюсюка, Володимир Григорович; Шевченко, Анна Олександрівна (My University, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women, reaching 20-25% [1, 2]. It is a multifaceted disease that affects various aspects of a woman's life, such as aesthetics, reproduction, metabolism, psychological well-being and sexuality [3].
Keywords: тези доповідей